You're bacon me crazy - Nelson, Suzanne, 1976- (Wish (Scholastic Inc.), 2016)
Tessa loves working at her aunt's trendy food truck, but when the city's big food festival gets canceled, the future of the truck is in question. Tessa, and the arrogant but frustratingly cute Asher must work together to save the food truck. Includes four bacon-themed recipes and suggestions for further reading.